Local Government Policy on Handling Stunting in Mandailing Natal Regency - Puansya, Irman; Pulungan, Darman Syah; Harahap, Rahmat HarisSaputra; Telaumbanua, Anita (Journal Corner of Education, Linguistics, and Literature, 2024)
Stunting is an issue that requires serious attention from the Central Government to the Regional Governments, particularly the Regional Government of Mandailing Natal Regency. This is because Mandailing Natal Regency is one of the regions in North Sumatra with a high stunting rate, reaching 47.7% in 2021, placing Mandailing Natal at the top rank in North Sumatra for stunting cases, according to the Indonesian Nutrition Status Study (SSGI). In 2022, Mandailing Natal dropped to third place with a stunting rate of 34.2%. However, this figure is still far from the national target set for Mandailing Natal, which is 14% by 2024. This study aims to analyze the policies of the Mandailing Natal Regional Government to reduce the stunting rate to 14% by 2024 and examine the various challenges faced. The method used in this research is qualitative descriptive analysis. Data collection techniques include interviews, observation, and documentation. The informants for this study included officials from the Mandailing Natal Health Office, Family Planning Office, village heads, and village assistants. The study found that the Mandailing Natal Government has implemented cross-sectoral policies, specific interventions, and the "Foster Father" program to reduce stunting. Success depends on policy continuity, program optimization, and increasing public awareness. The main challenges are limited funding, poor sanitation, and cultural barriers.